Law and constitutional guarantees in the Ecuadorian educational system of children and adolescents with disabilities - Parraga-Sánchez, José Dimas (International research journal of management, IT and social sciences, 2023)
Education is a fundamental right determined in the Universal Declaration of Human Rights of 1948; it is legally guaranteed for everyone without any discrimination. The objective of the work “Right and constitutional guarantees in the Ecuadorian educational system of children and adolescents with disabilities” is to analyze the effective measures for the applicability of constitutional rights and guarantees in the educational system of people with disabilities. For its preparation, the documentary theoretical review methodology with a qualitative approach was used, using Articles related to inclusive education, from the Ecuadorian Constitution, Organic Law of Disabilities, Organic Law of Intercultural Education, information from UNESCO and Human Rights; also national and foreign scientific information from the Dialnet, Scielo, Redalyc databases, referring to this topic, with 5 years of publication, Laws and Decrees of 1948 and 1994, and from 2006 to 2016, which are rights and regulations that are maintained valid until today. The result was that from the educational legal framework there is still a long way to go for the full application of education for people with disabilities; training is required for regular education teaching staff, provision of material resources and personalized pedagogical adaptations, and more work with the environment.